Eisenhower : a life - Johnson, Paul, 1928-2023; Davis, Jonathan, (Narrator); Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2014)
A portrait of the thirth-fourth president covers his years as a five-star general and his two presidential terms, as well as his Kansas childhood, West Point education, and volatile relationship with Richard Nixon.
Title from container.
Compact disc.
In container (17 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Narrated by Jonathan Davis.
Keywords: Eisenhower, Dwight D. -- 1890-1969; Presidents -- United States -- Biography; Generals -- United States -- Biography; Audiobooks